Implementasi Pembelajaran Berbasis Bermain untuk Meningkatkan Motivasi Belajar Siswa Kelas I Sekolah Dasar - Frida Ashofa; Lina Harishotul M; Isaroh Muchodimah; Joko Sulianto (STKIP Subang, 2026)
This study aims to analyze the implementation of play-based learning methods to improve the learning motivation of first-grade elementary school students. This research employed a descriptive qualitative approach involving 28 first-grade students and a classroom teacher as the main informant. Data were collected through direct observation, semi-structured interviews, and student questionnaires covering five indicators of learning motivation: attention, enthusiasm, curiosity, active participation, and perseverance. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with validity ensured through triangulation techniques. The results showed that the implementation of play-based learning, particularly through traditional costume puzzle activities and group discussions, significantly improved all indicators of student learning motivation. Students who were previously passive and easily distracted became more enthusiastic, actively engaged, and eager to participate in learning activities. These findings are consistent with Piaget's theory of concrete operational learning and Vygotsky's Zone of Proximal Development (ZPD), which emphasize the importance of concrete experience and social interaction in children's learning development. It is concluded that play-based learning is an effective alternative approach for lower-grade elementary school teachers to create active, enjoyable, and student-centered learning environments.